Threat as a feature in visual semantic object memory1. Issue 8 (25th March 2012) - Calley, Clifford S.; Motes, Michael A.; Chiang, H‐Sheng; Buhl, Virginia; Spence, Jeffrey S.; Abdi, Hervé; Anand, Raksha; Maguire, Mandy; Estevez, Leonardo; Briggs, Richard; Freeman, Thomas; Kraut, Michael A.; et al.
Abstract Threatening stimuli have been found to modulate visual processes related to perception and attention. The present functional magnetic resonance imaging (fMRI) study investigated whether threat modulates visual object recognition of man‐made and naturally occurring categories of stimuli. Compared with nonthreatening pictures, threatening pictures of real items elicited larger fMRI BOLD signal changes in medial visual cortices extending inferiorly into the temporo‐occipital (TO) "what" pathways. This region elicited greater signal changes for threatening items compared to nonthreatening from both the natural‐occurring and man‐made stimulus supraordinate categories, demonstrating a featural component to these visual processing areas. Two additional loci of signal changes within more lateral inferior TO areas (bilateral BA18 and 19 as well as the right ventral temporal lobe) were detected for a category–feature interaction, with stronger responses to man‐made (category) threatening (feature) stimuli than to natural threats. The findings are discussed in terms of visual recognition of processing efficiently or rapidly groups of items that confer an advantage for survival. Hum Brain Mapp, 2013. © 2012 Wiley Periodicals, Inc.